1997
DOI: 10.1002/(sici)1520-6343(1997)3:6<435::aid-bspy2>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Distinction of the two binding sites of serum transferrin by resonance Raman spectroscopy

Abstract: The resonance Raman (RR) data for a variety of transferrin samples were investigated to explore differences between the two active sites. The excitation wavelength dependence of the RR data in the low energy shift region (<900 cm−1) for diferric transferrin (Fe2Tf) reveals extensive changes in the relative intensities for some of the peaks, indicating that the visible and near ultraviolet absorption of the Fe2Tf protein is composed of several distinct transitions. The identity of the low‐energy vibrations was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…7a). The intensity pattern and frequencies of these bands correlate well with the ring deformation modes of a tyrosinate bound to Fe(III), as observed in other Fe(III)–tyrosinate proteins and related model complexes [23, 49, 61, 66–68]. Unfortunately, attempts to observe the Fe–O vibrations (500–600 cm −1 ) and the Fermi doublet (800–900 cm −1 ) characteristic of Fe(III)–phenolates were unsuccessful.…”
Section: Resultssupporting
confidence: 71%
“…7a). The intensity pattern and frequencies of these bands correlate well with the ring deformation modes of a tyrosinate bound to Fe(III), as observed in other Fe(III)–tyrosinate proteins and related model complexes [23, 49, 61, 66–68]. Unfortunately, attempts to observe the Fe–O vibrations (500–600 cm −1 ) and the Fermi doublet (800–900 cm −1 ) characteristic of Fe(III)–phenolates were unsuccessful.…”
Section: Resultssupporting
confidence: 71%
“…The majority of previous Raman spectroscopy studies of metal binding proteins, such as transferrin, have used resonance Raman to enhance the Raman signal arising from the presence of metal with wavenumbers below 900 cm −1 strongly influenced by the specific metal ligand. 11,12 More recently, iron saturation in transferrin 13 and differences between ferritin and magnetoferritin have been determined using the nonresonance Raman spectroscopy 14 and although both studies focused on Raman peaks arising from the presence of iron they also observed intense protein structure and polysaccharide associated peaks in the spectra.…”
Section: Introductionmentioning
confidence: 99%
“…While the free coordination sites in the apo-Tf skeleton are loaded with Fe 3+ -ions, additional vibration modes emerge in the Raman spectra of the protein. [25][26][27][28] The features from the spectra of Tf saturated with different Fe isotopes do not differ significantly which prevents the use of an isotope dilution approach. Therefore, the signal intensity ratio of the iron-related modes to the characteristic protein modes has now been evaluated for the first time in the quantitative analysis of the iron saturation in Tf.…”
Section: Introductionmentioning
confidence: 99%